Reduction of Hyperproduction of Thyroid Autoantibodies in Patients without Disturbance of the Thyroid Function: New Patents - A. Gerasun, Borys; A. Holubovska, Olga; Y. Hrytsko, Roman; N. Zinchuk, Olexandr; V. Shkurba, Andrij (Recent Patents on Endocrine, Metabolic & Immune Drug Discovery (Discontinued), 2014)
A new method of reduction of autoimmune process activity related to the thyroid in patients without signs of thyroiditis is presented in the article (patent of Ukraine No. 103742). New patents and inventions from different countries of the world related to the problem have been analysed. Materials and Methods: Sixty one patients with a significant disturbance of tolerance to the thyroid antigens in the absence of disturbance of the thyroid function were involved in the research. Twenty two patients with chronic hepatitis C, genotype 1 HCV, receiving antiviral therapy, were also included in the research. Patients were immunized intracutaneously with autoleukocytes for autoimmune process inhibition. After single immunization with autoleukocytes decrease in the level of antibodies against the thyroid antigens was observed in all patients. In some patients without chronic hepatitis C the levels of thyroperoxidase and thyroglobulin antibodies decreased by 50% and more (33.33% and 20.51%, respectively). In patients with ChHC these indices were considerably lower, and the duration of the achieved effect was shorter. However, immunization inhibited activity of immune process in patients with ChHC due to interferon therapy. The suggested method enables to decrease the threat for thyroiditis development even in patients with chronic hepatitis C during antiviral therapy.
Keywords: Autoimmune process